-10=5(a-1)-3a+1

Simple and best practice solution for -10=5(a-1)-3a+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=5(a-1)-3a+1 equation:


Simplifying
-10 = 5(a + -1) + -3a + 1

Reorder the terms:
-10 = 5(-1 + a) + -3a + 1
-10 = (-1 * 5 + a * 5) + -3a + 1
-10 = (-5 + 5a) + -3a + 1

Reorder the terms:
-10 = -5 + 1 + 5a + -3a

Combine like terms: -5 + 1 = -4
-10 = -4 + 5a + -3a

Combine like terms: 5a + -3a = 2a
-10 = -4 + 2a

Solving
-10 = -4 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-10 + -2a = -4 + 2a + -2a

Combine like terms: 2a + -2a = 0
-10 + -2a = -4 + 0
-10 + -2a = -4

Add '10' to each side of the equation.
-10 + 10 + -2a = -4 + 10

Combine like terms: -10 + 10 = 0
0 + -2a = -4 + 10
-2a = -4 + 10

Combine like terms: -4 + 10 = 6
-2a = 6

Divide each side by '-2'.
a = -3

Simplifying
a = -3

See similar equations:

| 1-g+5-2g+3G-6= | | 4x+n=8 | | 2n-102=8 | | 5(2z-7)=6z+17+4z | | 12x-32= | | 5x+x=2.4 | | 5(8-4x)=80 | | 2.5-h=h/2 | | 543-654g=69 | | -12=x-10 | | 10-2p=p-14 | | .2x=7-x | | 0=2(v+4) | | 95=5s | | 8(q+1)+3q=-14 | | 9x-5(x-3)=5x | | 2a-22=18 | | 6x-5+8w-2w=9w-24 | | 6y-2=3y+13 | | G(x+5)=(x+5)+2(x+5)+3 | | 11p=77 | | (-4X-6)(X-5)=0 | | 3(19-9)+5=35 | | 3640=x(1+0.05*6) | | -2r^2-10r-12=0 | | 3n+46=1+n | | 7-3r=28 | | 2x(x*x-2)+7x=9x+2x*x*x | | -5x+9=x-1 | | 0.5(4x+8)=x-7 | | 17=3(p-3)+8 | | x-3=45 |

Equations solver categories